2002
DOI: 10.1209/epl/i2002-00261-y
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional study of the Mott gap in the Hubbard model

Abstract: We study the Mott insulating phase of the one-dimensional Hubbard model using a local-density approximation (LDA) that is based on the Bethe Ansatz (BA). Unlike conventional functionals the BA-LDA has an explicit derivative discontinuity. We demonstrate that as a consequence of this discontinuity the BA-LDA yields the correct Mott gap, independently of the strength of the correlations. A convenient analytical formula for the Mott gap in the thermodynamic limit is also derived. We find that in one-dimensional q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 28 publications
3
125
0
Order By: Relevance
“…these wave vectors become For interacting systems in the thermodynamical limite, with theoretical maximum occupancy equal to two, Luttinger-liquid theory predicts that the oscillations occur with wave vector 2 if the interactions are weak, but 4 if they are strong enough to suppress double occupancy. Numerically, it was found that the crossover takes place around [7,8].…”
Section: Friedel Oscillations In the One-dimensional Hubbard Model VImentioning
confidence: 99%
“…these wave vectors become For interacting systems in the thermodynamical limite, with theoretical maximum occupancy equal to two, Luttinger-liquid theory predicts that the oscillations occur with wave vector 2 if the interactions are weak, but 4 if they are strong enough to suppress double occupancy. Numerically, it was found that the crossover takes place around [7,8].…”
Section: Friedel Oscillations In the One-dimensional Hubbard Model VImentioning
confidence: 99%
“…As a consequence and contrary to the EL-based LDA, the xc potential in Eq. (9) possesses a discontinuity in its derivative 16,51,52 .…”
Section: Balda/fnmentioning
confidence: 99%
“…This parametrization deviates somewhat from the exact, numerical XC energy of the Hubbard model [34,35], especially for weak interactions, but here we are not concerned about these differences. The crucial property for our purposes is the existence of a derivative discontinuity at half filling [36] (see discussion below).…”
Section: Model Hamiltonian For Time-dependent Transportmentioning
confidence: 99%